Comparative Genomics Reveals Accelerated Evolution in Conserved Pathways during the Diversification of Anole Lizards. (19th January 2018) - Tollis, Marc; Hutchins, Elizabeth D; Stapley, Jessica; Rupp, Shawn M; Eckalbar, Walter L; Maayan, Inbar; Lasku, Eris; Infante, Carlos R; Dennis, Stuart R; Robertson, Joel A; May, Catherine M; Crusoe, Michael R; et al.
Abstract: Squamates include all lizards and snakes, and display some of the most diverse and extreme morphological adaptations among vertebrates. However, compared with birds and mammals, relatively few resources exist for comparative genomic analyses of squamates, hampering efforts to understand the molecular bases of phenotypic diversification in such a speciose clade. In particular, the ∼400 species of anole lizard represent an extensive squamate radiation. Here, we sequence and assemble the draft genomes of three anole species— Anolis frenatus, Anolis auratus, and Anolis apletophallus —for comparison with the available reference genome of Anolis carolinensis. Comparative analyses reveal a rapid background rate of molecular evolution consistent with a model of punctuated equilibrium, and strong purifying selection on functional genomic elements in anoles. We find evidence for accelerated evolution in genes involved in behavior, sensory perception, and reproduction, as well as in genes regulating limb bud development and hindlimb specification. Morphometric analyses of anole fore and hindlimbs corroborated these findings. We detect signatures of positive selection across several genes related to the development and regulation of the forebrain, hormones, and the iguanian lizard dewlap, suggesting molecular changes underlying behavioral adaptations known to reinforce species boundaries were a key component in the diversification of anole lizards.